2019
DOI: 10.1021/acs.est.9b03159
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Environmental Occurrence, Fate, and Toxicity of Novel Brominated Flame Retardants

Abstract: Use of legacy brominated flame retardants (BFRs), including polybrominated diphenyl ethers (PBDEs) and hexabromocyclododecane (HBCD), has been reduced due to adverse effects of these chemicals. Several novel brominated flame retardants (NBFRs), such decabromodiphenyl ethane (DBDPE) and bis­(2,4,6-tribromophenoxy) ethane (BTBPE), have been developed as replacements for PBDEs. NBFRs are used in various industrial and consumer products, which leads to their ubiquitous occurrence in the environment. This article r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
117
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(127 citation statements)
references
References 170 publications
1
117
0
9
Order By: Relevance
“…It has been reported that a major issue with DecaBDE is its ability to be degraded by UV to the known toxic penta- and octa-congeners [ 8 , 14 , 15 ], which again suggests that there are differences of C–Br bond energies within the same molecule. Obviously if BrFRs are to be able to be biologically degraded to non-toxic products, the means of either weakening C–Br bonds and /or rendering them more amenable to enzymatic reduction to bromide ions should be better understood.…”
Section: Organobromine Flame Retardants—environmental Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that a major issue with DecaBDE is its ability to be degraded by UV to the known toxic penta- and octa-congeners [ 8 , 14 , 15 ], which again suggests that there are differences of C–Br bond energies within the same molecule. Obviously if BrFRs are to be able to be biologically degraded to non-toxic products, the means of either weakening C–Br bonds and /or rendering them more amenable to enzymatic reduction to bromide ions should be better understood.…”
Section: Organobromine Flame Retardants—environmental Challengesmentioning
confidence: 99%
“…Xiong et al [ 8 ] have recently reviewed the whole issue regarding the fate of a number of brominated flame retardants in the environment including literature regarding their exposure in both abiotic, including air, water, dust, soil, sediment and sludge, and biotic matrices, including bird, fish, and human serum. Furthermore, they review the effects of photodegradation, thermal degradation and biodegradation.…”
Section: Organobromine Flame Retardants—environmental Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…2021, 11, 3837 2 of 12 in production and usage in 2001, while more recent information is not readily available [15]. Increasing use of DBDPE and BTBPE as flame retardants has resulted in their frequent and widespread occurrences in various environments [16]. DBDPE and BTBPE have been detected in Chinese wastewater at levels up to 22.3 ng/L and 2.2 ng/L, respectively [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of bromine in BFRs leads to many challenges whether on health and safety, due to their toxicity, or on their proper disposal or recycling. Indeed, the occurrence of most BFRs in various environmental matrices can cause adverse effects on diverse organisms through different modes of action, such as hormone disruption and genotoxicity (Kim et al, 2014;Xiong et al, 2019). Incineration has the disadvantage of generating corrosive or gases and possibly highly toxic dioxins (Sakai et al, 2001;Ni et al, 2012).…”
Section: Introductionmentioning
confidence: 99%